The Application of the Soft Approach Method in the Prevention of Radicalism - Lintang, Janiar Arsyaddillah; Muriman S, Chairul; Runturambi, Arthur Josias Simon (International Journal of Social Service and Research, 2025)
The development of information technology, including social media, is believed to have become a fertile medium for the spread of radicalism, intolerance, and terrorism. Digital and social media are considered capable of changing a person's character in a short time through the content they share. This study aims to determine the application of the soft approach method implemented by the Bekasi City Metro Police in an effort to prevent radicalism. The research employs a qualitative method by applying data collection techniques through interviews, observations, and documentation. The results of this study indicate that the soft approach method implemented by the Bekasi City Metro Police in preventing radicalism is still not optimal. Therefore, concrete steps are needed to improve it through the enhancement of soft approach methods in the prevention of radicalism, including strengthening counter-radical and deradicalization programs, improving the performance of Bhabinkamtibmas, increasing the internalization of Pancasila values, and strengthening the state defense program. Furthermore, to enhance cooperation in the implementation of soft approaches to preventing radicalism, efforts can be made through the empowerment of work units dealing with radicalism or terrorism, increasing the exchange of intelligence information between units, establishing MoUs with local governments for radicalism prevention, and developing integrated programs to strengthen government institutions against the spread of radicalism.